2020
DOI: 10.1155/2020/1025952
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Effect of Coal Microstructures on the Macroscopic Mechanical Behavior

Abstract: This paper investigates the influence of mineral structure on macromechanical behavior of coal under different loading conditions using X-ray CT scanning experimental and numerical methods. The three-dimensional (3D) reconstruction of coal was conducted to assess the spatial distribution characteristics of the mineral structure by AVIZO software. Based on fractal box dimension (BCD) and equivalent diameter, the mineral structures were quantitatively characterized. The 3D finite element models with three distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The geometry, size, and distribution of irregular minerals in coal are primary factors that constitute its heterogeneity characteristics and significantly influence the macroscopic mechanical behavior of coal. The specific influence of minerals on the mechanical behavior of coal has been investigated by constructing finite element models containing different mineral structures and performing uniaxial compression simulations. , The results showed that the larger the size and higher the content of minerals, the more complex the distribution. Under uniaxial conditions, the presence of minerals and the increase in mineral sizes increase the peak strength, elastic modulus, and residual strength of coal (Figure ).…”
Section: Qualitative Evaluation Of Macroscopic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The geometry, size, and distribution of irregular minerals in coal are primary factors that constitute its heterogeneity characteristics and significantly influence the macroscopic mechanical behavior of coal. The specific influence of minerals on the mechanical behavior of coal has been investigated by constructing finite element models containing different mineral structures and performing uniaxial compression simulations. , The results showed that the larger the size and higher the content of minerals, the more complex the distribution. Under uniaxial conditions, the presence of minerals and the increase in mineral sizes increase the peak strength, elastic modulus, and residual strength of coal (Figure ).…”
Section: Qualitative Evaluation Of Macroscopic Propertiesmentioning
confidence: 99%
“…Relationship between macroscopic mechanical behavior of coal and microscopic parameters of minerals. [Modified with permission from refs (Copyright 2020, The Authors, published by Journal of Mining & Safety Engineering ) and (Copyright 2020, Y. Fu and Z. Feng. Authors under Creative Commons Attribution 4.0 International License (CC BY 4.0)).…”
Section: Qualitative Evaluation Of Macroscopic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation